Testing the impact of hatha yoga on task switching: a randomized controlled trial - Szaszkó, Bence; Schmid, Rebecca Rosa; Pomper, Ulrich; Maiworm, Mira; Laiber, Sophia; Lange, Max Josef; Tschenett, Hannah; Nater, Urs Markus; Ansorge, Ulrich (Frontiers in Human Neuroscience, 2024)
Switching attention between or within tasks is part of the implementation and maintenance of executive control processes and plays an indispensable role in our daily lives: It allows us to perform on distinct tasks and with variable objects, enabling us to adapt to and respond in dynamically changing environments. Here, we tested if yoga could benefit switching of attention between distinct objects of one's focus (e.g., through practicing switching between one's own body, feelings, and different postures) in particular and executive control in general. We therefore conducted a randomized controlled trial with 98 participants and a waitlisted control group. In the intervention group, healthy yoga novices practiced Hatha yoga 3x a week, for eight weeks. We conducted two experiments: A purely behavioral task investigating changes in behavioral costs during switching between attentional control sets (74 participants analyzed), and a modality-switching task focusing on electrophysiology (EEG data of 47 participants analyzed).At the electrophysiological level, frequency-tagging indicated no interventional effect on participants' ability to switch between the auditory and visual modalities. However, increases in task-related frontocentral theta activity, resulting from the intervention, indicated an ability to increasingly deploy executive resources to the prioritized task when needed. At the behavioral level, our intervention resulted in more efficient holding of target representations in working memory, indicated by decreased mixing costs. Again, however, intervention effects on switching costs were missing. We, thus, conclude that Hatha yoga has a positive influence on executive control, potentially through improvements in working memory rather than directly on switching.